Why is squint surgery in children in decline?. Issue 4 (18th March 2004) - MacEwen, C J; Chakrabarti, H S
Abstract : Background/aims: Paediatric squint surgery appears to be declining. This study aims to identify if this is so and, if so, why. Methods: Retrospective review of (1) episodes of paediatric squint surgery in Scotland and Tayside, 1986–2001, (2) presentations to orthoptists (Tayside) during 1986 and 1996. Results: (1) Overall, a 58% fall in surgery in Scotland and 59% in Tayside. For esotropia, a reduction of 63% (Scotland) and 69% (Tayside). (2) Incidence of esotropia was unchanged; surgery for these esotropes fell (from 55% to 30%) (p = 0.013). More children received maximum hypermetropic correction (p <0.001) and more developed stereopsis (p = 0.003). Conclusion: Childhood strabismus surgery, particularly for esotropia, is declining. The maximum hypermetropic correction has improved the functional results.